PENGEMBANGAN MEDIA INTERAKTIF PADA MATA PELAJARAN KOMPUTER DAN JARINGAN DASAR DI SMKN 5 BATANGHARI - Yogi Irdes Putra; Ahmad Ridoh; Fauziah Zi; Radinal Fadli (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2020)
The purpose of this study was to develoved an Interactive Media on basic computers and networks Subjects and test whether the media can better improve the basic computers and networks. A four-D Research and Development (R & D) study had been applied to develop and test the validity, practicality, and effectiveness of the Interactive Media inteaching basic computers and networks. The steps consisted of define; design; develop; and disseminate. The testing for content validity of the Interactive Media was found valid. Based on the teachers and the students response on the practicality, it was found that this media was found highly practical. Based on the learning outcomes the effectiveness of the media was found effective. Based on the data analysis, it was found that the Interactive Media can better improve the students' learning outcome on the basic computers and networks for Grade X at SMKN 5 Batanghari.